Early Experience of Undertaking Robotic Assisted Total Mesorectal Excision in Rectal Resections, Avoiding a Diverting Stoma: Key eHancement of the Anastomosis for No Stoma Technique — A Case Series. (April 2023) - Waqas, Ahmad; Mykoniatis, Ioanis; Sidiqi, Najaf; Ahmed, Anwar; Stefan, Samuel; Naqvi, Syed; Harper, Mick; Khan, Jim
Background. Anastomotic leak is a feared complication in rectal cancer surgery, and a proximal diverting stoma to protect the rectal anastomosis is used to minimize its impact. We evaluated a novel technique that uses the da Vinci® robotic platform (Intuitive Surgical) to reinforce the colorectal anastomosis and rectal staple line with sutures, and rectal resection and assessment of the anastomotic perfusion, using our Portsmouth protocol. Methods. During robotic rectal cancer surgery, we used indocyanine green to determine the level of transection and check the vascularity of the circular anastomosis. The distal transverse staple line and circular staple line of the colorectal anastomosis were reinforced with absorbable interrupted stitches (KHANS technique – Key enHancement of the Anastomosis for No Stoma). The integrity of the colorectal/anal anastomosis was also checked using the underwater air-water leak test, with concomitant flexible sigmoidoscopy to visualize the circular staple line. Results. Fifty patients underwent total mesorectal excision for cancer. Using the KHANS technique, we avoided a diverting stoma in all cases. One patient had a radiological leak, leading to a pelvic abscess. In 56% of cases, the anastomosis was within 5 cm of the anal verge. Median length of stay was 5 (3-34) days, with two 30-day readmissions. No 90-day mortality or 30-day reoperations were observed. Conclusion. The KHANS technique appears feasible, successful, and safe in decreasing the incidence of diverting stomas in rectal resections.